Development of indicators for evaluating the effectiveness of the monitoring system for development of standardization documents using information technology - A. V. Knyazev; Yu. Yu. Cheremukhina (Омский научный вестник)
The article presents the results of the development of indicators for monitoring the process of developing standardization documents. An integral part of the management of the standardization document development process is the monitoring system. The monitoring system allows you to monitor and control key indicators of the standardization document development process. Also, the use of a monitoring system makes it possible to form a reference base for analyzing the causes of deviations in the values of indicators. At the same time, an important task is to evaluate the effectiveness of the monitoring system and the mathematical justification of the indicator for evaluating the effectiveness of the monitoring system, taking into account errors in the implementation of the monitoring process.